2020
DOI: 10.17759/autdd.2020180103
|View full text |Cite
|
Sign up to set email alerts
|

Attitude to co-Education of Children with Disabilities and Healthy Children in Students of Pedagogical Specialties

Abstract: The article examines the attitude of students of pedagogical specialties to inclusive education, examines the causes of negative attitudes and identifies students’ perceptions of the psychological qualities of people who are in favor and against inclusive education. The author’s questionnaire used as a research method. The survey involved students of Yaroslavl State Pedagogical University named after K.D. Ushinsky and Rostov Pedagogical College. The results obtained in the study showed that the majority of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…The disadvantage of the mutual information algorithm is that it is greatly affected by the input edge probability [19], which can also be seen from Formula (11).…”
Section:    mentioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantage of the mutual information algorithm is that it is greatly affected by the input edge probability [19], which can also be seen from Formula (11).…”
Section:    mentioning
confidence: 99%
“…Simanovskij A E derived a model for describing the topology of public opinion based on complex network theory. The results showed that the proposed model can well reflect the distribution of public opinion [11]. Zhang Y used artificial intelligence technology to design a public opinion monitoring system.…”
Section: Introductionmentioning
confidence: 99%